APAKAH ANDA BENAR-BENAR MENGENALI PESAING ANDA? - Setiadi Umar (Center for Economic Studies Universitas Katolik Parahyangan, 2005)
Paying attention to competitor is as important as caring your customers. By giving full attention ONLY to customers and not aware of what your competitors doing will create a very fragile condition. Since, as we know, what we called satisfaction, expectation, and customer value is very relative to competitors offering. Their values are not absolute. There are many companies who have lack information about their competitor. Many do not even know, whether they have competitor or not. It is because they are the only one of their kind or because they are market nicher. According to Levitt, these enterprises are suffering what he called marketing myopia. Actually (in the real situation) they do have competitor in the greater context. Even though their products are not similar, however they do serve similar need.